2004
DOI: 10.1111/j.1476-4431.2004.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia–reperfusion injury pathophysiology, part I

Abstract: Objective: To review the current scientific literature on ischemia–reperfusion (IR) injury in both human and veterinary medicine. To describe the normal antioxidant defense mechanisms, the pathophysiology of IR injury, and the role of neutrophils in IR injury. Data sources: Data sources include scientific reviews and original research publications in both human and veterinary medicine. Summary: IR injury is a complex pathophysiological process involving numerous pathways and body systems. Normal antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 114 publications
(222 reference statements)
2
55
0
4
Order By: Relevance
“…[25] Thus, ROS are believed to play a central role in I/R injury in addition to several other diseases, including neoplasia, atherosclerosis, and neurodegenerative diseases. [8] ROS are capable of reacting with proteins, lipids, and nucleic acids leading to the lipid peroxidation of biological membranes, which in turn impacts upon enzymatic processes such as ion pump activity [15,26] . Previous experiments show that various exogenous antioxidant agents such as allopurinol, melatonin, tocopherol, leflunomide, and some flavonoids have the potential to reduce I/R induced-renal injury and help the improvement of kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Thus, ROS are believed to play a central role in I/R injury in addition to several other diseases, including neoplasia, atherosclerosis, and neurodegenerative diseases. [8] ROS are capable of reacting with proteins, lipids, and nucleic acids leading to the lipid peroxidation of biological membranes, which in turn impacts upon enzymatic processes such as ion pump activity [15,26] . Previous experiments show that various exogenous antioxidant agents such as allopurinol, melatonin, tocopherol, leflunomide, and some flavonoids have the potential to reduce I/R induced-renal injury and help the improvement of kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…antioxidant systems. [8] Like other cells, kidney cells have these antioxidant defenses to cope with potential oxidative damages. Unfortunately, the level of these endogenous enzymes and antioxidant compounds become insufficient during I/R events due to abundant ROS formation.…”
Section: Introductionmentioning
confidence: 99%
“…2,39,[41][42][43] Reactive oxygen and nitrogen species are believed to play a central role in I/R injury in addition to several other factors, such as neutrophils, platelets, the coagulation system and the xanthine-oxidoreductase enzyme system. Our previous report demonstrated that renal I/R worsened the renal dysfunction, oxidative stress and histopathologic features in rats.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many scientists report that renal I/R injury is a common cause of renal cell death, acute renal failure and, in the case of transplantation, delayed graft function or graft rejection. [2][3][4] Many mediators are involved in the pathophysiology of I/R injury, including reactive oxygen species (ROS), reactive nitrogen species (RNS), purine metabolites, neutrophil accumulation, vasoactive substance (endothelin, angiotensin II) and subsequent release of lytic enzymes. [5][6][7] Nitric oxide (NO), a soluble, free radical gas, has an astounding range of biological roles, including modulation of vascular tone and inflammation.…”
mentioning
confidence: 99%
“…Embora seja necessária para a sobrevivência celular, a reperfusão cria mais injúria do que a isquemia em decorrência da grave disfunção endotelial que promove. A disfunção endotelial resulta da maciça formação de radicais livres, diminuição da liberação de óxido nítrico e acentuada liberação de endotelina, criando um estado de intensa vasoconstrição e consequente diminuição da perfusão periférica (MCMICHAEL;MOORE, 2004).…”
Section: Isquemia Hipóxia Tecidual E Reperfusãounclassified